PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH LOBSTER AIR TAWAR (Cherax quadricarinatus) YANG DIBERI PAKAN BUATAN BERBAHAN BAKU TEPUNG KEONG MAS (Pomacea sp.) - mulyana mulyana1; rosmawati rosmawati; muhammad azmi rafi (JURNAL MINA SAINS, 2019)
This reasearch has been conducted at The Fisheries Laboratory, Agricultural Faculty, Djuanda University, Bogor, on December 2016 – May 2017. The research is aimed to knowthe best concentration of  Keong Masshell mealto increase the growth rate and survival rate of freshwater lobster. The experimental research used completely randomized design with 4 treatments and 3 replications. The treatments were  K (the commercial shrimp artificial feed), A (the artificial feed with 5% the shell meal of Keong Mas), B the artificial feed with 7% the shell meal of Keong Mas), and C (the artificial feed with 9% the shell meal of Keong Mas). The test shrimp were the freshwater Lobster sized 3.5 – 4.5 cm and was fed at satiation twice a day. The daily growth rate, the feed efficiency, survival rate, and water quality has been observed. The results of research showed there were not a  significantly different between the treatments (P>0.05) against the daily growth rate, the feed efficiency, and survival rate of the freshwater Lobster.The shell meal of Keong Mas could be as a Calcium source. The Keong Mas meal can subtitute 100% fish meal of artificial feed thus could be the alternate standard material of the fish meal of the freshwater Lobster feed.Water quality in aquaculture media still on the range of feasible for the freshwater Lobster culture. Keywords: Freshwater Lobster, Keong Mas, Feed, Growth